Context-based learning in the formation of subject competence at the bioinorganic chemistry lessons - Клименко, Світлана (Pedagogy of Higher and Secondary Education, 2014)
Klimenko S. A. Context-based learning in the formation of subject competence at the bioinorganic chemistry lessons. The article covers peculiarities of using context-based learning with the purpose of providing professional orientation in teaching bioinorganic chemistry and the formation of subject competence. The characteristic to the construction evaluation of learning process through the activities is given. The active methods and forms of organization of learning activities that promote the implementation of contextual learning were proposed.